Does a 3-minute all-out test provide suitable measures of exercise intensity at the maximal lactate steady state or peak oxygen uptake for well-trained runners? - Sperlich, B.; Zinner, C.; Trenk, D.; Holmberg, H. C. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To examine whether a 3-min all-out test can be used to obtain accurate values for the maximal lactate steady state (vMLSS) and/or peak oxygen uptake (VO2peak) of well-trained runners. Methods: The 15 male volunteers (25 ± 5 y, 181 ± 6 cm, 76 ± 7 kg, VO2peak 69.3 ± 9.5 mL/kg·min) performed a ramp test, a 3-min all-out test, and several submaximal 30-min runs at constant paces of vEND (mean velocity during the last 30 s of the 3-min all-out test) itself and vEND +0.2, +0.1, -0.1, -0.2, -0.3, or -0.4 m/s. Results: vMLSS and vEND were correlated (r = .69, P = .004), although vMLSS was lower (mean difference: 0.26 ± 0.32 m/s, 95% CI -.44 to -.08 m/s, P = .007, effect size = 0.65). The VO2peak values derived from the ramp and 3-min all-out tests were not correlated (r = .41, P = .12), with a mean difference of 523 ± 1002 mL (95% CI -31 to 1077 mL). Conclusion: A 3-min all-out test does not provide a suitable measure of vMLSS or VO2peak for well-trained runners.